AUTHENTIC MATERIALS FOR BIOLOGY STUDENTS: A NEED ANALYSIS IN ESP TEACHING - Adijaya Made Aryawan (Universitas Pendidikan Ganesha, 2017)
The present paper is attempting to reveal the students’ need towards the authentic materials in ESP teaching at Biology Department of Ganesha Univeristy. There were 154 students taken as the subjects of the study. The primary data were gained from the responses given by the respondents through questionnaire, while the secondary data were taken from documents study on the curriculum, and syllabus of ESP, and interview in order to get the justification and clarification towards some selection on the questionnaire. The data show that the students need authentic materials such as newspaper article, scientific journal, international papers, internet, technical documents, manual, textbook, and grammar textbook. In spite of the authenticity, it is considered to able to promote students’ motivation and bridging the gap between the classroom situation and real life purposes.